Drama, Performance, and Polity in Pre-Cromwellian Ireland. - Fletcher, Alan J. (Studies in early English drama., 2000)
A study of the early history of drama and performance in Ireland, from the 7th century through the 16th and 17th centuries, ending on the eve of the arrival of Oliver Cromwell.